Learning Failures and Barriers in Schools During a Pandemic at Indonesia: A Literature Review - Purba Wahyu Adi; Trisno Martono; Sudarno Sudarno (Neolectura, 2021)
The effectiveness of learning during the Covid-19 pandemic experienced obstacles and triggered the failure of the teaching and learning process in schools. Students are directly affected and if left for a long time will experience learning loss. This study aims to describe the obstacles that trigger failure in learning in schools during the pandemic in Indonesia through a literature review. Searching research journal data using Google Scholar database from various available journals. Article criteria can be in the form of qualitative and quantitative approaches. There are no restrictions on the year of publication or the use of language. In this literature study, 20 articles have been screened by authors. The results of the review generally describe learning barriers during the pandemic, namely; pedagogical barriers, barriers to facilities and infrastructure, internal barriers to students, and barriers to the external environment of students.